Reduced Factor V Concentration and Altered FV1/FV2 Ratio do not fully Explain R2-associated APC-resistance - Govers-Riemslag, José W. P.; Castoldi, Elisabetta; Nicolaes, Gerry A. F.; Tans, Guido; Rosing, Jan (Thrombosis and Haemostasis, 2002)
Carriership of the factor V (FV) R2 haplotype is associated with mild APC-resistance, moderately reduced FV levels and a relative increase of the more thrombogenic FV isoform, FV1. Since low FV levels and increased FV1 can theoretically cause APC-resistance, we investigated whether these alterations can quantitatively account for R2-associated APC-resistance. In order to determine the effect of FV concentration and FV isoform composition on the APC-response, we reconstituted FV-deficient plasma with purified FV1 and FV2 in different molar ratios and to varying FV concentrations. APC sensitivity ratios (APCsr) were determined with the Coatest® APCTM Resistance V, which probes the effect of APC on both FV-a and FVIIIa-inactivation, and with the Immunochrom® APC response test, which only quantifies the effect of APC on FVIII(a)-inactivation. In both assays, low FV concentrations and/or high relative amounts of FV1 rendered plasma samples more resistant to APC. APCsr were also determined in FVdeficient plasma reconstituted with purified FV at levels and isoform ratios observed in R2-homozygotes (98% FV, 42% FV1) and agematched controls (119% FV, 26% FV1). In both tests the APCsr of reconstituted control plasma was the same as that of plasma from controls, whereas reconstituted R2-plasma was less APC-resistant than plasma from homozygous carriers of the R2 haplotype. We conclude that the low FV levels and altered FV isoform ratio cannot fully explain R2-associated APC-resistance.
Keywords: APC-resistance; FV isoforms; R2 haplotype; factor VIII